2010
DOI: 10.1007/s11250-010-9633-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and growth of Malpura ewes subjected to thermal and nutritional stress

Abstract: A study was conducted to assess the effect of combined stresses (thermal and nutritional) on physiological adaptability and growth performance of Malpura ewes. Twenty-eight adult Malpura ewes (average BW 33.56 kg) were used in the present study. The ewes were divided into four groups, viz., GI (n=7; control), GII (n=7; thermal stress), GIII (n=7; nutritional stress), and GIV (n=7; combined stress). The animals were stall-fed with a diet consisting of 60% roughage and 40% concentrate. GI and GII ewes were provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 22 publications
6
57
0
3
Order By: Relevance
“…However, the mean RR was greater during the dry than during the rainy season. The RT is influenced by the time of day, as AT is greater during the afternoon (Sejian et al 2010;Silva et al 2010). In the dry season, afternoon RR was 36.3 mov/min, indicating that the animals were not subjected to considerable stress during this period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mean RR was greater during the dry than during the rainy season. The RT is influenced by the time of day, as AT is greater during the afternoon (Sejian et al 2010;Silva et al 2010). In the dry season, afternoon RR was 36.3 mov/min, indicating that the animals were not subjected to considerable stress during this period.…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies on the effect of season on biochemical blood parameters (Sejian et al 2010;Ribeiro et al 2016). In our study, these parameters were significantly different between seasons (p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…However, both plasma T3 and T4 significantly reduced in GIII as compared to both GI and GII kids, reflecting the severity of nutritional stress in GIII kids. It is an established fact that depression of thyroid function during stress was part of the process of metabolic adaptation, by which the heat production may consequently be maintained at low level [30,31]. In addition, blood thyroid hormones are considered to be good indicators of the nutritional status of an animal [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed that other physiological parameters, such as circulating concentrations of thyroid hormones can change depending on the environmental conditions (VERÍSSIMO et al, 2009;MAURYA et al, 2010;KOLUMAN;DASKIRAN, 2011). These hormones are directly involved with metabolic rate regulation and obligatory thermogenesis, thus they have an essential role in thermoregulation and homeothermy.…”
Section: Introductionmentioning
confidence: 99%